The Social Dimension of Shopping Centres in South Africa - Daphne Ntlhe (Profesional Muda Cendekia Publishing, 2023)
Shopping centres have transformed consumers’ consumption patterns, behaviour, and spatial trips. Consumers’ shopping trips have shifted from traditional shopping streets to shopping centres. Their decision to patronise a shopping centre is generally influenced by a set of attributes that consumers consider commanding them to visit the centre. These attributes or reasons establish a shopping centre’s role in a neighbourhood. This paper aims to analyse consumers’ reasons for visiting shopping centres, their visits companions, and the frequency of their visits to the shopping centres as determinant factors for township shopping centres as entertainment spaces in South Africa. The study contributes to the literature on shopping centres in townships outside of South Africa’s metropolitan areas. A questionnaire survey was employed to acquire data from 390 consumers in Namakgale Crossing using the convenient sampling technique. The study concludes that township shopping centres play an entertainment and social role in addition to their economic role.